Neojihadist visual politics: comparing YouTube videos of North Caucasus and Uyghur militants - Vergani, M.; Zuev, D. (Asian Studies Review, 2015)
YouTube videos offer a rare opportunity to gain an insight into the sequestered world of neojihadism. This study examines and compares the lines of the visual narrative associated with two Asian insurgencies that help to form the global Islamic social movement: the insurgency in Chechnya (North Caucasus) and that in Xinjiang (China). The purpose of the article is to describe the narratives used by the Islamic militants addressing the conflict and to identify similarities and differences in the use of visual rhetorical techniques by neojihadist groups to propagate their worldview. The study of the visual narratives promoted in the videos will help to provide a better understanding of the impact of the neojihadist narratives on the creation of collective identities. Our findings suggest that these narratives have similar features, which can be identified in a set of sub-narratives. Within the common pattern, however, significant differences can be found, especially in the interpretation of the videos by the audiences.